THE EFFECT OF SELF-CONCEPT ON THE STUDENTS’ ENTREPRENEURSHIP POTENTIAL - Yani, Dwi Ari; Sayuti, Muhammad; Achsan, Bambang Noor (Universitas Ahmad Dahlan, 2019)
Entrepreneurship contributes to economic development in any country and can be linked to economic growth. The increasing number of young entrepreneurs is needed to support the growth of the world economy. Universities realize the importance of developing students' entrepreneurial potential. This study aims to determine the effect of self-concept of the potential college student entrepreneurship. This research is a quantitative study. The formulation of the problem is whether self-concept influences the entrepreneurial potential of students. The research subjects were students of the Akademi Kesejahteraan Sosial (AKK) with majors in culinary, fashion and cosmetology. In achieving its objectives, an online questionnaire was given to 60 students. The data collected is analyzed in simple regression model. Data were analyzed with SPSS 16 version. The results showed that self-concept has a positive and significant impact on the potential of entrepreneurship. The academy can strengthen students' self-concept by instilling entrepreneurial values and training to form a good self-concept.